TRIPLE OPPRESSION ON WOMEN IN TONI MORRISON’S TAR BABY AND THE BLUEST EYE - Aytemis DEPCİ (Fırat University, 2019)
This article intends to interpret Morrison’s novels, Tar Baby and The Bluest Eye considering primarily the black women’s oppression and their struggles in the oppressive environments they inhabit as well as the white womens positining in the patriarchal society. This study discusses the effects of Western beauty concept on the characters of Morrison’s both novels as a universal standard requiring whiteness in American society which leads self destruction and sexual objectification of women. Morrison’s both novels elaborate domestic violence, rape and white beauty standards. However, The Bluest Eye solely concentrates on black feminist problems while her novel Tar Baby also stresses the suppression of white women along with the black women’s issues. White or black, all women experience different kind of subordination and varying levels of oppression. No matter what class, race or position in the society they have, someone as desperate as Pecola in The Bluest Eye and as beautiful and successful as Jadine or though being white and beautiful like Margaret in Tar Baby, women are treated as subordinate by men. However, the African American women’s position in the society seems harsher than white women in general since they experience triple oppression as race, class and gender simultaneously. Therefore, questioning the impact of class differences, gender oppression and racism and also the differences of skin color which elevates the status of those light skinned blacks whereas aggravates the sufferings of the ones with the darker skins, both within the black community and within society as a whole is critical to understand the black women’s positioning.